Tingkat Kelelahan Pengemudi Bus Rapid Transport (BRT) Jakarta Berdasarkan Swedish Occupational Fatigue Index (SOFI) - Rida Zuraida (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Fatigue is a common situation experienced by everyone, but until now a simple measuring tools universally accepted is not exist. Fatigue measurement instrument most widely used is an instrument-based questionnaire. This study used the Swedish Occupational Fatigue Index (SOFI) as one of the instrument to measure BRT driver’s fatigue. The aim is to evaluate physical mental, and shift work fatigue and provide an overview of fatigue levels experienced by the driver BRT on two different shifts. Hopefully it can be used for driver fatigue management by a company. The study was conducted for two different shifts (morning and afternoon), with a total participants are 30 drivers. Results showed that motivation level of shift 2-driver is lower after they finish their work compared to shift1-driver. In shift 1, generally available time to rest,socializing and hanging out with family is longer than available time for shift 2-driver. Perception of loss of energy after work is also higher in shift 2 compared to shift 1, especially the perception of feeling exhausted. Similar results were obtained in the physical aspect and the physical exertion and physical discomfort. Therefore we can conclude the work shift has affected fatigue level experienced by the driver's BRT, and shift rotation is suggested to help the driver to recuperate.